Further development of expert system for application of iso 11745 brazing for aerospace applications — qualification test for brazers and brazing operators — brazing of metallic components - Aung, Naing Htoo (2017)
As brazing become more widely used in aerospace industry, need for robust and strong qualification process arises in order to assure the safety and structural integrity of the aircraft. One of the widely used standard qualification process for aerospace brazing is known as ISO 11745 Brazing for Aerospace Applications — Qualification test for Brazes and Brazing Operators — Brazing of metallic components. This standardization describes the details step by step requirement of the minimum degree of manual skill and technical knowledge.